Association between inter-arm difference in SBP and central blood pressure in a Beijing community cohort. Issue 1 (February 2021) - Ma, Wei; Qi, Litong; Fan, Fangfang; Yang, Ying; Zhang, Baowei; Jia, Jia; Li, Min; Zhang, Yan; Huo, Yong
Abstract : Objective: The inter-arm SBP difference (IASBPD) can serve as a predictor of cardiovascular disease (CVD). In this study, we aimed to determine the relationship between IASBPD and central blood pressure (CBP). Methods: The study cohort comprised of 7842 eligible individuals. Their BPs were assessed simultaneously in both arms using an Omron BP-203RPEIII vascular profiler, and the IASBPD was measured as the absolute difference in these values (absolute value of left minus right). The CBP was noninvasively measured using an Omron HEM-9000AI device. Multivariate regression analysis was used to assess the association between the central SBP (cSBP) and the IASBPD. Results: An IASBPD of ≥10 mmHg was positively associated with the cSBP ( β  = 2.26; 95% confidence interval, 1.04–3.48; P  < 0.001). The interaction test showed no significant interactions between the IASBPD and any of the assessed covariates (age group; sex; BMI; smoking status; heart rate group; the presence of hypertension, diabetes, or CVD; and antihypertensive drug use) when the cSBP was used as the outcome in the subgroup analysis. Conclusion: The mechanism underlying the ability of the IASBPD to predict CVD may partly involve an increase in the CBP.